(untitled) (diségno, 2024)
Kosmos [1] by Alexander von Humboldt (1769-1859) –the geographer born in Berlin to whom we owe the modern concept of landscape– evokes a ‘doctoral passion’ in me: it was, in fact, during the years in which I was working on my thesis for the doctoral program in Survey and Representation of the Built Environment that, driven by a growing interest in the complex issues present in the concept of landscape, I came across this fundamental text. [read more]